Avicenna's optimistic theodicy - T.K. Ibrahim (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The greatest representative of falsafa (Islamic peripatetism, or aristotelianism) Avicenna (Abu Ali Ibn Sina, 980–1037) was the first Muslim philosopher who elaborated the theory of evil. According to his theodicy, the good explicitly predominates in the world created by the omnibenevolent God, while the evil exists as something relative and accidental, as a necessary concomitant of the substantial good. Justifying the idea of our world as the best of all possible worlds, Ibn Sina anticipated the famous Leibnizian concept of optimus mundus. The philosopher expanded this optimistic view also in his soteriology. Inspired by the Quran's teaching on the all-comprising character of divine mercy, he proposed an apocatastasis concept, which was a very bold one in the medieval theologized society. In this perspective, he argued also about the possibility of afterlife's spiritual (intellectual) perfection, which helps a human being the achievement of the highest degree of happiness. In this paper, a systematic analysis of Avicennas' teaching has been performed and the evolution of his views on the problem of salvation has been traced. The main attention has been paid to the part “Theology” (or “Metaphysics”; Arabic: al-Ilahiyyat) of his encyclopedic work “The Healing” (ash-Shifa') and, especially, of his late major treatise “Remarks and Admonitions” (al-Isharat wa-t-tanbihat). The influence of this conception on further development of philosophy and theology in Islam and its significance for the reformation and modernization of the contemporary Muslim thought have been emphasized.